Interactive removal of bacterial and viral particles during transport through low-cost filtering materials - Chen, Xijuan; Yang, Liqiong; Guo, Junjie; Xu, Shuang; Di, Junzhen; Zhuang, Jie (Frontiers in Microbiology, 2022)
Pathogen filtration is critically important for water sanitation. However, it is a big challenge to balance removal efficiency and filtering material cost. In this study, we quantified the removal processes of a bacterial strain Escherichia coli 652T7 and a model bacteriophage MS2 (15597-B1) during their transport through columns containing iron filings (IF), calcined magnesite (CM), natural ore limestone (OL) or corn stalk biochar (BC) under saturated flow conditions. Experimental results showed that 99.98%, 79.55%, 63.79%, 62.59% of injected E. coli 652T7 and 98.78%, 92.26%, 68.79%, 69.82% of injected MS2 were removed by IF, CM, OL, and BC, respectively. The differences in removal percentage were attributed to the disparities of the microorganisms and filtering materials in surface function groups, surface charges, and surface morphology. Transport modeling with advection-dispersion equation (ADE) and interaction energy calculation with XDLVO model indicated that E. coli 652T7 and MS2 were mostly removed via irreversible attachment. In IF columns, E. coli 652T7 promoted the transport of MS2 but not vice versa. In CM columns, MS2 facilitated the transport of E. coli 652T7 and vice versa at a less extent. Such changes were a combined result of attachment site competition, steric effect, and mechanical straining. We found that the sum of the removal percentages of the two microorganisms in their respective transport experiments were similar to those calculated from their co-transport experiments. This result suggests that the removals were mainly limited by the attachment sites in the filtering materials.